Pengaruh Metode Applied Behaviour AnalisysTerhadap Tingkat Kepatuhan Anak Autis Di Pusat Layanan Autis Sragen - guswiyamto, Guswiyanto; , Agus Widodo, S.Fis, M.Kes (2015)
WITH AUTISM ON THE COMPLIANCE LEVEL" V BAB, 48 Pages, 2 Pictures, 6 Tables (Supervised by Agus Widodo, SFis.,MKes and Umi Budi Rahayu, Fis.,MKes) Background: The complexity of handicap on based grow concept for fetus until baby under 3th years old must be monitoring and evaluation of two parents, family and medical team. Because of these can be predicted as teh condition of BEHAVIOR , compliance, IQ and etc. So remember a few years latest many terms of dissability on growth of baby can be detected. One of them is autism, that was as the igoring spectrum dissability on BEHAVIOR thatcan makedisturb physic and psychys of babies. One of method that can be prepare was applied behavior analysis for compliance level on baby with autism. Objective: This study aimed to know applied behavior analysis can prepare for compliance level on baby with autism. Methods: This study was pre experimental, research design with pre test post test one group design. Technique of sampling is purposive sampling. Number of population 34 respondens and get sample 10 respondens with autism in PLA Sragen. Number of men was 5 patients and women 5 patients, that's range of age 2-10 years old. All of 10 respodens given assesment with form of applied behavior analysis, pre and post do the ABA. Statistic test by the Wilcoxon Signed Ranks Test. The research at July 2015 (one month) Results: Based on statistical tested of Wilcoxon Signed Ranks Test get significancy result 0.005 where p < 0.05. It's mean Ha is accepted. The ABA can give compliance level babies with autism. Conclusions: There is a significant the ABA can give compliance level babies with autism. Keywords: The ABA, autism, compliance level